Uprighting Severe Premaxilla Retrusion in Bilateral Complete Cleft Lip and Palate Patient : A Case Report - Siriphan, Natchanon; Worawiwat, Chinnawes; Ritthagol, Wipapun (Thai Journal of Orthodontics, 2023)
The differences in developmental characteristics of premaxilla in the bilateral/ unilateral complete cleft lip and palate should be taken into consideration prior to initiation of any orthodontic treatment. In regards to bilateral complete cleft lip and palate, the small premaxilla solely attaches to the vomer bone at the superior surface. These lead to obviously increase in mobility and instability of the premaxilla as compared to unilateral complete cleft lip and palate. Regarding the premaxillary growth pattern variations in the bilateral complete cleft lip and palate, the growth can be predominantly classified into; (1) Class II pattern with forward and downward movement of premaxilla, and (2) Class III pattern with backward and downward movement of premaxilla. The comprehensive orthodontic treatments using either removable or fixed orthodontic appliance are suitable treatment modalities for these patients. The purpose of this article is to demonstrate an alternative treatment approach in a rare case of severely retruded premaxilla in bilateral complete cleft lip and palate patient utilizing modified orthodontic appliance.